Employment of women and demand-side forces - Donna K. Ginther; Chinhui Juhn (Federal Reserve Bank of Atlanta, 2001)
Using the 1964–95 March Current Population Surveys and the 1940–90 Census, this paper examines the relationship between female employment growth and changes in labor demand. Specifically, the authors examine whether industrial change and changes in labor demand can account for both the acceleration and deceleration of female employment growth across the decades as well as the pattern of biased growth in favor of more skilled women. They find that labor demand proxies are successful in accounting for the pattern of biased growth but are less successful in accounting for the overall acceleration of female employment, particularly in the 1970s.
Keywords: 330; Labor supply; Women - Employment